Precipitation in a Nanograined 7475 Aluminium Alloy—Processing, Properties and Nanoanalysis1. Issue 5 (17th April 2014) - Lewandowska, Malgorzata; Wawer, Kinga; Kozikowski, Pawel; Ohnuma, Masato; Kurzydlowski, Krzysztof J.; Zschech, Ehrenfried
<x xml:space="preserve">Abstract</x> The precipitation phenomena in 7475 nanograined aluminium alloy was analysed by means of microhardness measurements, small angle X‐ray scattering and electron microscopy. The nanograined samples were obtained by the hydrostatic extrusion of solution annealed and water quenched samples. It has been established that low temperature ageing causes precipitation processes to occur. However, the precipitation phenomena in nanograined materials proceed differently to those in micrograined materials. Moreover, the particle strengthening is limited by enhanced grain boundary precipitation which does not contribute to an increase in strength (when dislocation slip is the dominant deformation mechanism) and by the smaller size of precipitates.